2011
DOI: 10.1021/jp204497p
|View full text |Cite
|
Sign up to set email alerts
|

Excited Electronic States, Transition Probabilities, and Radiative Lifetimes of CAs: A Theoretical Contribution and Challenge to Experimentalists

Abstract: High-level CASSCF/MRCI calculations with a quintuple-ζ quality basis set are reported by characterizing for the first time a manifold of electronic states of the CAs radical yet to be investigated experimentally. Along with the potential energy curves and the associated spectroscopic constants, the dipole moment functions for selected electronic states as well as the transition dipole moment functions for the most relevant electronic transitions are also presented. Estimates of radiative transition probabiliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The single-reference CC hierarchy breaks down whenever a single determinant becomes an improper zeroth-order description of the system, whereas multireference methods lack a systematic hierarchy comparable to CC theory. The standard schemes, beyond second-order perturbation theory, still rely on multireference configuration interaction (MRCI) with approximate size-extensivity corrections. The extension of coupled-cluster theory to multireference cases, on the other hand, is not straightforward, and only recently have a number of implementations been reported that are capable of treating realistic systems. In this context, the multireference coupled-cluster (MRCC) theory , should provide a very reliable way to treat systems with such complex electronic structure.…”
Section: Introductionmentioning
confidence: 99%
“…The single-reference CC hierarchy breaks down whenever a single determinant becomes an improper zeroth-order description of the system, whereas multireference methods lack a systematic hierarchy comparable to CC theory. The standard schemes, beyond second-order perturbation theory, still rely on multireference configuration interaction (MRCI) with approximate size-extensivity corrections. The extension of coupled-cluster theory to multireference cases, on the other hand, is not straightforward, and only recently have a number of implementations been reported that are capable of treating realistic systems. In this context, the multireference coupled-cluster (MRCC) theory , should provide a very reliable way to treat systems with such complex electronic structure.…”
Section: Introductionmentioning
confidence: 99%
“…Other properties that have a smaller impact on cooling efficiency such as harmonic frequencies, spin-orbit splittings, and electronic energies were also predicted with comparable accuracy. A comparison between the predictions of the MRCISD+Q/aV5Z level of theory for the CAs molecule [32] and experimental measurements [33] shows that calculated bond lengths are within 1 pm of experimental values therefore the calculations for TeH + should be more accurate than the ones for SbH.…”
Section: Molecular Structurementioning
confidence: 87%
“…FCFs depend most strongly on the difference in equilibrium bond length between electronic states, and the equilibrium bond lengths for SbH were predicted to within 3 pm of the measured values. A comparison between the predictions of the MRCISD+Q/aV5Z level of theory for the CAs molecule [32] and experimental measurements [33] shows that calculated bond lengths are within 1 pm of experimental values; therefore, the calculations for TeH + should be more accurate than the ones for SbH. For optical cooling, we also rely on short lifetimes.…”
Section: Molecular Structurementioning
confidence: 94%